2015
DOI: 10.3892/ijo.2015.2949
|View full text |Cite
|
Sign up to set email alerts
|

Let-7a inhibits growth and migration of breast cancer cells by targeting HMGA1

Abstract: Let-7 is one of the earliest discovered microRNAs (miRNAs) and has been reported to regulate self renewal and tumorigenicity of breast cancer cells. Let-7a is a member of this family and its function has not been fully characterized in breast cancer. First, total RNAs of breast cancer cells (MDA-MB-231, MCF-7), breast cancer tissues and corresponding adjacent normal tissues were extracted and used to detect let-7a expression by qRT-PCR. Secondly, the effects of let-7a on proliferation, colony formation, migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 52 publications
4
53
0
Order By: Relevance
“…HMGA1 is primarily expressed in fetal tissues (Hynes et al, 1994) and many cancer tissues, such as colorectal cancer (Williama et al, ), breast cancer (Cianfrocca et al, ), pancreatic cancer (Piscuoglio et al, ), ovarian cancer (Liu et al, ), and prostate cancer (Zhang et al, ). In this study, we found that HMGA1 expression in breast cancer tissues was stronger than that in normal breast tissues, which is consistent with the previous reports on breast cancer cell lines and breast cancer tissues (Liu et al, ; Sepe et al, ). Furthermore, we found that HMGA1 played an important role in the progression of breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…HMGA1 is primarily expressed in fetal tissues (Hynes et al, 1994) and many cancer tissues, such as colorectal cancer (Williama et al, ), breast cancer (Cianfrocca et al, ), pancreatic cancer (Piscuoglio et al, ), ovarian cancer (Liu et al, ), and prostate cancer (Zhang et al, ). In this study, we found that HMGA1 expression in breast cancer tissues was stronger than that in normal breast tissues, which is consistent with the previous reports on breast cancer cell lines and breast cancer tissues (Liu et al, ; Sepe et al, ). Furthermore, we found that HMGA1 played an important role in the progression of breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Elevated let-7 is subsequently maintained in various adult tissue [17]. In contrast, decreased expression of let-7 has been detected in human cancers, including hepatocellular carcinoma, breast cancer, and lung cancer [18][19][20], possibly indicating the reverse embryogenesis process occurs during tumorigenesis [21].…”
Section: Introductionmentioning
confidence: 99%
“…Let-7 family, including let-7d, was reported to inhibit tumor pathogenesis [20,22]. On the other hand, let-7d contributes to the pathogenesis of some cancers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that let‐7a is poorly expressed in glioma when compared with that of a normal healthy brain . Additionally, compared with the adjacent normal tissues, let‐7a expression is found to be reduced in breast cancer tissues . A previous study presented evidence highlighting the down‐regulation of let‐7f in glioma cells and tissues .…”
Section: Discussionmentioning
confidence: 99%